KARAKTER DISIPLIN SISWA DITINJAU DARI PERSEPSI KETAHANAN KELUARGA DAN KUALITAS KEHIDUPAN SEKOLAH - Siti Salma Salsabila; Rachmy Diana (UIN Sunan Kalijaga, 2021)
Discipline character is very crucial to be developed since an early age. Children who have a disciplined character will be able to learn and to develop admirable behavior that is accepted by society and members of social groups. This study examined whether family resilience and the quality of school life has a correlation with the character of discipline. The hypotheses were (1) there is a positive correlation between the quality of school life and family resilience with the disciplinary character of students (2) there is a positive correlation between the quality of school life and the character of student discipline and (3) there is a positive correlation between family resilience and the character of student discipline. This research was conducted by giving three scales to 220 junior high school students. The result analysis showed that the hypotheses were accepted. There was a positive and significance correlation between family resilience and the quality of school life with the disciplinary character of students.Keywords: discipline character; family strengths; quality school of lifeKarakter disiplin sangat penting dikembangkan sejak dini. Hal ini dikarenakan anak yang memiliki karakter disiplin mampu belajar berperilaku yang diterima oleh masyarakat dan anggota kelompok sosial. Penelitian ini ingin menguji apakah karakter disiplin dipengaruhi oleh ketahanan keluarga dan kualitas kehidupan sekolah. Hipotesis dalam penelitian ini adalah (1) terdapat hubungan positif kualitas kehidupan sekolah dan ketahanan keluarga dengan karakter disiplin siswa (2) terdapat hubungan positif kualitas kehidupan sekolah dan karakter disiplin siswa dan (3) terdapat hubungan positif ketahanan keluarga dan karakter disiplin siswa. Penelitian ini dilakukan dengan memberikan tiga skala kepada 220 siswa Sekolah Menengah Pertama. Hasil analisis menunjukkan bahwa terdapat hubungan positif antara ketahanan keluarga dan kualitas kehidupan sekolah dengan kualitas kehidupan sekolah. Kata kunci : Karakter disiplin, ketahanan keluarga, kualitas kehidupan sekolah